Transport of Glyphosate and Aminomethylphosphonic Acid under Two Soil Management Practices in an Italian Vineyard. Issue 5 (1st September 2016) - Napoli, Marco; Marta, Anna Dalla; Zanchi, Camillo A.; Orlandini, Simone
Abstract : Worldwide, glyphosate is the most widely used herbicide in controlling the growth of annual and perennial weeds. An increasing number of studies have highlighted the environmental risk resulting from the use of this molecule in aquatic and terrestrial ecosystems. The objective of the study was to determine the transport of glyphosate and its degradation product, aminomethylphosphonic acid (AMPA), through runoff and transported sediment from a vineyard under two different soil management systems: harrowed inter‐row (HR) and permanent grass covered inter‐row (GR). The study was performed over a period of 4 yr. Glyphosate and AMPA concentrations were found to be higher in runoff and in transported sediment from HR compared with GR, regardless of the amount of runoff and transported sediment. The mean annual percentages of glyphosate loss, via runoff and transported sediment, were about 1.37 and 0.73% for HR and GR, respectively. Aminomethylphosphonic acid represented approximately 30.9 and 40.0% of the total glyphosate losses in GR and HR, respectively. Moreover, results suggested that rains occurring within 4 wk after treatment could cause the transport of glyphosate and AMPA in high concentrations. Soil analyses indicated that glyphosate content was below detection within 1 yr, whereas AMPA remained in the soil profiles along the vine row and in the inter‐row. Results indicated that GR can reduce soil and herbicide loss by runoff in vineyard cropping system. Core Ideas: Transport of glyphosate and AMPA were assessed on grass‐covered and harrowed inter‐rows. Glyphosate was below detection in 1 yr, whereas AMPA was recovered in the soil profiles. Permanent grass cover reduced significantly the yearly glyphosate and AMPA losses.